A post-deregulation analysis of wages in US freight transportation - Steffen Habermalz; Kristen Monaco (Institute for the Study of Labor (IZA), 2007)
After a period of regulatory changes in the early 1980s we are faced with new freight transportation labor markets in the U.S. Using data from the 1984-1999 Current Population Survey, we examine trends in the wages of workers within freight transportation, with a focus on wage differentials across industries and occupations. Our aim is to provide stylized facts. We find that real wages in rail, truck, and water transport declined over most of the period and have rebounded since 1996. Within industries we find considerable persistence in wage differentials between and within a majority of occupations. We also find evidence of increased competition in a subset of labor markets
urn:nbn:de:101:1-20080425501
Keywords: 330; Güterverkehrsgewerbe; Arbeitsrecht; Deregulierung; Lohnstruktur; Reallohn; USA